BASIC CONCEPTS OF VIRTUAL AND ADDED REALITY IN TEACHING INFORMATION (Web of Technology: Multidimensional Research Journal, 2024)
Virtual laboratories and simulations are becoming the main tool for studying complex subjects such as chemistry and physics, where dangerous experiments can be safely reproduced. AR, on the contrary, adds digital elements to a real-life setting, making it useful for studying visualization-related disciplines such as anatomy or history, where students can see real-time reconstructions of objects or events. An important advantage of AR is accessibility: mobile devices make this technology available for widespread use both in schools and at home.